2018
DOI: 10.19184/jpe.v11i2.6454
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Media Bervariasi Dan Motivasi Belajar Terhadap Hasil Belajar Mata Pelajaran Ekonomi Siswa Kelas Xi Ips Sma Negeri 2 Jember Tahun Pelajaran 2016/2017

Abstract: AbstrakTujuan dalam penelitian ini adalah (1) untuk mengetahui pegaruh yang signifikan dari variabel penggunaan media bervariasi terhadap motivasi belajar siswa kelas XI IPS SMA Negeri 2 Jember Tahun Pelajaran 2016/2017, 2) untuk mengetahui pengaruh yang signifikan dari variabel penggunaan media bervariasi terhadap hasil belajar siswa kelas XI IPS SMA Negeri 2 Jember Tahun Pelajaran 2016/2017, 3) untuk mengetahui pengaruh yang signifikan dari variabel motivasi belajar terhadap hasil belajar siswa kelas XI IPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 0 publications
0
12
0
24
Order By: Relevance
“…With the existence of student learning motivation, it will automatically have an impact on student learning outcomes. This statement is supported by the results of research conducted by Widiasih et al, (2018) which states that learning motivation has a significant effect on learning outcomes. Research conducted by Adriani, (2018) shows that motivation has a positive impact on learning outcomes.…”
Section: Discussionmentioning
confidence: 61%
“…With the existence of student learning motivation, it will automatically have an impact on student learning outcomes. This statement is supported by the results of research conducted by Widiasih et al, (2018) which states that learning motivation has a significant effect on learning outcomes. Research conducted by Adriani, (2018) shows that motivation has a positive impact on learning outcomes.…”
Section: Discussionmentioning
confidence: 61%
“…This article emphasizes the importance of these two variables in an effort to improve student learning outcomes. The research of Widiasih et al, (2018) shows that varied media and student motivation have an impact on learning outcomes in economic subjects. The use of various media has a positive and significant effect on learning motivation.…”
Section: Resultsmentioning
confidence: 99%
“…The present research underlines both variables to improve the students' learning outcomes. Widiasih et al, (2018) showed variated media and students' learning motivation give a significant impact on economic learning outcomes. The use of variated media gives a positive influence on learning motivation and learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Pada dasarnya ketika semua unsur ini dirancang dengan baik maka siswa semakin tertarik dan termotivasi untuk belajar. Motivasi dalam media pembelajaran dinilai sangat penting dan harus ada pada setiap media pembelajaran yang berkualitas, karena motivasi mampu membangun pembelajaran yang lebih bermakna bagi siswa (Risabethe, 2016;Widiasih, Widodo, & Kartini, 2018). Dengan demikian multimedia interaktif ini dapat digunakan untuk memancing siswa aktif dan termotivasi untuk belajar secara mandiri.…”
Section: Gambar 1 Multimedia Interaktif Yang Dikembangkanunclassified